2019
DOI: 10.7150/jca.30386
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Predicting Lymph Node Metastasis in T1 Breast Cancer based on the Surveillance, Epidemiology, and End Results Program

Abstract: Background: Patients with early stage breast cancer with lymph nodes metastasis were proven to have more aggressive biologically phenotypes. This study aimed to build a nomogram to predict lymph node metastasis in patients with T1 breast cancer. Methods: We identified female patients with T1 breast cancer diagnosed between 2010 and 2014 in the Surveillance, Epidemiology and End Results database. The patients were randomized into training and validation sets. Univariate and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…The role of SLNB is controversial. According to the literature, approximately 60% to 85% of early breast cancer cases are node negative, thus would not benefit from SLNB [1,2,5,[22][23][24][25][26]. In our study, 85.0% of the cases were node-negative, and axillary surgical interventions were unnecessary.…”
Section: Discussionmentioning
confidence: 53%
“…The role of SLNB is controversial. According to the literature, approximately 60% to 85% of early breast cancer cases are node negative, thus would not benefit from SLNB [1,2,5,[22][23][24][25][26]. In our study, 85.0% of the cases were node-negative, and axillary surgical interventions were unnecessary.…”
Section: Discussionmentioning
confidence: 53%
“…According to previous studies, an AUC of the ROC curve >0.7 indicated that the built nomogram had a good accuracy and an acceptable discrimination. 16,17 In addition, calibration plots showed that the predicted DM probability was identical to the actual observation. Thus, the built nomogram incorporating clinicopathological characteristics was proved to have an appealing sensitivity and specificity in predicting the risk of DM.…”
Section: Discussionmentioning
confidence: 73%
“…To test the performance of our nomogram, ROC curves were generated in both the training and validation sets. According to previous studies, an AUC of the ROC curve >0.7 indicated that the built nomogram had a good accuracy and an acceptable discrimination 16,17 . In addition, calibration plots showed that the predicted DM probability was identical to the actual observation.…”
Section: Discussionmentioning
confidence: 75%
“…For patients with no enlarged lymph nodes in the central compartment before surgery, ultrasound doctors often relax their vigilance in the assessment of lateral lymph nodes and can easily omit to skip metastasis. Previous studies [ 13 , 16 18 ] have reported that tumor located in the upper portion and with tumors diameter of no larger than 1 cm were closely linked to skip metastasis, and suggested that patients with the above risk factors should be carefully evaluated for lymph node status. Unfortunately, these studies did not give the probability of skip metastasis in these patients, or what kind of patients needed to undergo prophylactic LLN dissection.…”
Section: Introductionmentioning
confidence: 99%